Possible Implication of Bacterial Infection in Acute Graft-Versus-Host Disease after Allogeneic Hematopoietic Stem Cell Transplantation - Fuji, Shigeo; Kapp, Markus; Einsele, Hermann (Frontiers in Oncology, 2014)
Graft-versus-host disease (GVHD) is still one of the major causes of morbidity and mortality in allogeneic hematopoietic stem cell transplantation (HSCT). In the pathogenesis of acute GVHD, it has been established that donor-derived T cells activated in the recipient play a major role in GVHD in initiation and maintenance within an inflammatory cascade. To reduce the risk of GVHD, intensification of GVHD prophylaxis like T cell depletion is effective, but it inevitably increases the risk of infectious diseases and abrogates beneficial graft-versus-leukemia effects. Although various cytokines are considered to play an important role in the pathogenesis of GVHD, GVHD initiation is such a complex process that cannot be prevented by means of single inflammatory cytokine inhibition. Thus, efficient methods to control the whole inflammatory milieu both on cellular and humoral view are needed. In this context, infectious diseases can theoretically contribute to an elevation of inflammatory cytokines after allogeneic HSCT and activation of various subtypes of immune effector cells, which might in summary lead to an aggravation of acute GVHD. The appropriate treatments or prophylaxis of bacterial infection during the early phase after allogeneic HSCT might be beneficial to reduce not only infectious-related but also GVHD-related mortality. Here, we aim to review the literature addressing the interactions of bacterial infections and GVHD after allogeneic HSCT.